Study of the properties of self-sustaining nuclear chain reaction in the fuel-containing masses of the "Ukryttya" object for the case of varying velocity of water inflow - V. A. Babenko; V. N. Pavlovych (Ядерна фізика та енергетика)
The main peculiarities of ignition and development of self-sustaining nuclear chain reaction (SCR) in fuel-containing masses (FCM) of Chernobyl "Ukryttya" were studied for the case of varying velocity of water incoming into the system or its outcoming. On the basis of analysis and numerical solution of the corresponding system of differential equations for the main characteristics of the system, it was shown that the variations of water inflow could lead to very sufficient and various changes in SCR development comparing to possible modes at constant velocities of water inflow. In particular, the calculations show that the neutron bursts with great amplitude could take place in the system under definite sufficiently reasonable physical conditions. It was also shown that the increase of velocity of water inflow into the FCM in the mode of constant oscillations can lead to transition into "beyond critical" state which is the subcritical state with big quantity of water.